Differences in clinical characteristics and prognosis of Penicilliosis among HIV-negative patients with or without underlying disease in Southern China: a retrospective study. Issue 1 (December 2015) - Qiu, Ye; Liao, Haifei; Zhang, Jianquan; Zhong, Xiaoning; Tan, Caimei; Lu, Decheng
Abstract Background The incidence of Penicillium marneffei infection has recently increased. This fungus can cause fatal systemic mycosis in both immunocompetent and immunocompromised patients without HIV infection. Methods We retrospectively analysedPenicilliosis patients between January 1, 2003 and August 1, 2014 at the First Affiliated Hospital of Guangxi Medical University. HIV-negative patients withPenicilliosis were divided into two groups: patients with underlying disease (Group D) and patients without underlying disease (Group ND). HIV-positive patients were excluded. The relationships between overall survival and the study variables were assessed using univariate and multivariate analyses. Results During 11 years, Penicillium marneffei infection was diagnosed in 109 patients. Sixty-six (60.55 %) patients were HIV-positive and excluded from these cases. Forty-three patients were HIV-negative were enrolled. Among these patients, 18 (41.86 %) patients were in Group D, and 25 (58.14 %) were in Group ND. The most common underlying disease was diabetes. There were no statistically significant differences between the two groups in clinical characteristics, except for immune state and prognosis. Group ND had higher lymphocyte cell counts, CD4 cell counts, and CD4 T-cell percentages than Group D (P < 0.05). Patients in Group D had higher recurrence and mortality rates than Group ND (P < 0.05). In the univariate analysis, only underlying disease, CD4 cell percentage, and T lymphocyte cell percentage were significantly associated with overall survival. Conclusions Penicillium m arneffei can infect HIV-negative patients and can cause fatal systemic mycosis. There were no clear differences in clinical manifestations among HIV-negative patients with and without underlying disease. However, Penicillium marneffei in HIV-negative patients in with underlying diseases may cause immune function decline and a deficiency in T-cell-mediated immunity. Underlying disease, CD4 cell percentage, and T lymphocyte cell percentage may be potential risk factors affecting prognosis. Timely, effective, and longer courses of antifungal treatments are important in improving prognoses.